2014
DOI: 10.1136/archdischild-2013-305519
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of bubble CPAP in neonatal care in low and middle income countries: a systematic review

Abstract: There is evidence that bubble CPAP is safe and reduces the need for mechanical ventilation. Further research into the efficacy of bubble CPAP in low-income and middle-income countries is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 38 publications
3
122
0
1
Order By: Relevance
“…Martin et al 1 report an important systematic review of studies evaluating bubble continuous positive airway pressure (CPAP) for the treatment of neonatal respiratory distress in resource-limited countries. The authors conclude ‘bubble CPAP is a promising intervention which reduces the need for high cost mechanical ventilators… however there is need for more research into the impact of bubble CPAP on neonatal mortality and into effective implementation methods...’ An implication is made that further prospective trials in resource-limited settings are needed.…”
mentioning
confidence: 99%
“…Martin et al 1 report an important systematic review of studies evaluating bubble continuous positive airway pressure (CPAP) for the treatment of neonatal respiratory distress in resource-limited countries. The authors conclude ‘bubble CPAP is a promising intervention which reduces the need for high cost mechanical ventilators… however there is need for more research into the impact of bubble CPAP on neonatal mortality and into effective implementation methods...’ An implication is made that further prospective trials in resource-limited settings are needed.…”
mentioning
confidence: 99%
“…Chen et al 5 performed an economic evaluation to determine the cost-effectiveness of a low-cost bubble CPAP device and suggest that in a Malawian setting bubble CPAP is a highly cost-effective strategy especially for very low birthweight infants, and infants with respiratory distress syndrome or sepsis. Martin et al 6 conducted a systematic review of the safety and efficacy of bubble CPAP in neonatal care in low-income and middle-income countries. The majority of studies were case series but they identified four randomised trials, two conducted in India (N=30 and N=114),7 8 one in Iran (N=50)9 and one in South America (N=256) 10.…”
Section: Discussionmentioning
confidence: 99%
“…Low-cost bCPAP has recently been developed 3. A recent systematic review of bCPAP in LMICs concluded that bCPAP reduces the need for mechanical ventilation in neonates with respiratory distress in tertiary hospitals, but found no adequate controlled studies of whether CPAP lowers mortality in neonates compared with standard-flow supplemental oxygen therapy 4. This review included a recent small non-randomised trial of infants with respiratory distress and birth weight >1 kg in Malawi of a low-cost bCPAP compared with standard nasal oxygen therapy if no device was available 5.…”
Section: Bubble Cpapmentioning
confidence: 99%